Trajectories of women's abortion-related care: A conceptual framework. (March 2018) - Coast, Ernestina; Norris, Alison H.; Moore, Ann M.; Freeman, Emily
Abstract: We present a new conceptual framework for studying trajectories to obtaining abortion-related care. It assembles for the first time all of the known factors influencing a trajectory and encourages readers to consider the ways these macro- and micro-level factors operate in multiple and sometimes conflicting ways. Based on presentation to and feedback from abortion experts (researchers, providers, funders, policymakers and advisors, advocates) (n = 325) between 03/06/2014 and 22/08/2015, and a systematic mapping of peer-reviewed literature (n = 424) published between 01/01/2011 and 30/10/2017, our framework synthesises the factors shaping abortion trajectories, grouped into three domains: abortion-specific experiences, individual contexts, and (inter)national and sub-national contexts. Our framework includes time-dependent processes involved in an individual trajectory, starting with timing of pregnancy awareness. This framework can be used to guide testable hypotheses about enabling and inhibiting influences on care-seeking behaviour and consideration about how abortion trajectories might be influenced by policy or practice. Research based on understanding of trajectories has the potential to improve women's experiences and outcomes of abortion-related care. Highlights: Synthesis of influences on trajectories to abortion-related care is lacking. A new conceptual framework for studying trajectories to obtaining abortion-related care. The framework includes all known factors influencing abortion care-seeking. A framework built on expert consultation and a systematic literature mapping.